2017
DOI: 10.5489/cuaj.4420
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilateral renal function preservation following minimally invasive partial nephrectomy: The effect of tumour characteristics and warm ischemic time

Abstract: Introduction: The relative impact of preoperative and perioperative variables on renal function following partial nephrectomy (PN) is controversial. To further investigate, we assess the effects of tumour complexity, warm ischemic time (WIT), and volume of resected renal parenchyma on ipsilateral renal function (IRF) outcomes following minimally invasive PN. Methods: Of patients who underwent laparoscopic or roboticassisted PN between 2002 and 2011 at our institution, 99 met our inclusion criteria. The effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Given this, fWIT may be a better parameter than WIT alone. In the urologic literature, there is a substantial amount of research showing that fWIT of >30 minutes may increase kidney damage vs <30 minutes . We found that most patients who successfully donated had fWIT <30 minutes and that fWIT remains low even with increasing WIT ( P = NS, Figure ).…”
Section: Discussionmentioning
confidence: 74%
“…Given this, fWIT may be a better parameter than WIT alone. In the urologic literature, there is a substantial amount of research showing that fWIT of >30 minutes may increase kidney damage vs <30 minutes . We found that most patients who successfully donated had fWIT <30 minutes and that fWIT remains low even with increasing WIT ( P = NS, Figure ).…”
Section: Discussionmentioning
confidence: 74%